Horizontal and Vertical Distribution of Chlorophyll phaeophytine and Bacteria in The Natural Borg Islam During Spring and Summar - Ightiyar, samar; Durgham, Hani; Alali, Bader (Latakia University Journal -Biological Sciences Series, 2016)
general study of counted Bacteria and Chlorophyll a Give us an initial picture to the environment safety and vitality of marine environmental, which constitutes one of the basic components. In this paper, we show the most important results related to horizontal and vertical changes of temperature and counted Bacteria, the concentrations of dyes Chlorophyll a,phaeophytine and relationships between them to depth of 300 m. The study showed a high degree in deep-water temperature reached to about two degrees in recent decades. as well as significant decrease in counted Bacteria (800 - 12750CFU / 100 ml) and dyes Chlorophyll a (under detection threshold - 0.24 mg / l) and phaeophytine (under the detection threshold - 0.064 mg / l), which refers to the weakness in the wild tributaries and low nutrients that reaches to the beaches and marine wealth , which reflect the negative impacts on marine environment. تعطي دراسة التعداد العام للبكتيريا، والأصبغة اليخضورية صورة أولية عن سلامة البيئة المدروسة، و المخزون الحيوي الأولي للنظام البيئي البحري الذي تشكل أحد مكوناته الأساسية. نعرض في هذا البحث أهم النتائج المتعلقة بالتغيرات الأفقية و العمودية للحرارة، و التعداد العام للبكتيريا، و تراكيز الأصبغة اليخضورية و السمراوية، و العلاقات المتبادلة بينها وذلك حتى عمق300 م. أظهرت الدراسة ارتفاع درجة حرارة المياه العميقة بمقدار درجتين مئويتين تقريباً خلال العقود الأخيرة، إضافة إلى انخفاض كبير في التعداد العام للبكتيريا (800 – 12750CFU/100 ml)، و الأصبغة اليخضورية (تحت عتبة الكشف –0.24 ملغ/ل) و السمراوية (تحت عتبة الكشف –0.064 ملغ/ل)،والذي يشير إلى ضعف في الروافد البرية وانخفاض في المغذيات الواصلة إلى الشواطئ البحرية، وماله من تأثيرات سلبية في البيئة البحرية المدروسة.